Impact of Social Media on Adolescence: Mapping Emerging Needs to Build Resilient Skills - Falcón-Linares, Carolina; González-Yubero, Sara; Mauri-Medrano, Marta; Cardoso-Moreno, María Jesús (Societies (Basel, Switzerland), 2023)
It is important to study the impact of social media on mental health and well-being, as most young people use social media. Research has provided evidence of the link between social media and mental health, identifying vulnerability variables, risk factors, comorbidity, and predictors of deterioration or improvement. However, there is still very little qualitative insight into young people’s experiences and perceptions of social media and its impact on their subjective well-being. This study consists of a systematic review of the literature and a narrative synthesis of scientific articles published between 2013 and 2023 and indexed in the most important scientific databases in our field of knowledge. The SALSA protocol for systematic reviews of scientific literature was followed. We worked on a final sample of 25 articles, all of which were qualitative in methodology. From the content analysis, we extracted five thematic categories that describe and explore in depth the complex impact of social networks on adolescents’ well-being. The interactions between positive and negative effects, as well as the links with protective or vulnerability factors, are presented with the aim of constructing as complete a knowledge framework as possible. The paper concludes with useful implications for educational interventions.